Use of Durian leaf infused (Durio zibethinus) as natural anesthetic for Gouramy fish (Osphronemus gouramy) in dry transportation - Handajani, Hany; Prasetyo, Dony; Hastuti, Sri Dwi; Fahimuridlo, Muhammad (Universitas Malikussaleh, 2022)
Purpose the research to know influence giving leaf durian infused to anesthesia process gurami fish with weight 100-150 gr use predetermined dosage by upper threshold test and lower threshold test. Then, use formula EC-100 (Effektivity Consentrastion) to know fainting time fish and conscious time fish. On threshold test use among others concentrate 1000ppm, 2500ppm, 5000ppm and 7500ppm. That at concentration 7500ppm is upper threshold because gurami fish die by soaking leaf Durian infused for 24 hours while at concentration 5000pm is lower threshold because gurami fish not die by soaking leaf Durian infused for 48 hours. Next to search concentration row with use formula EC-100 and than available concentrate 5400ppm, 5900ppm, 6400ppm, 6900ppm and 7400ppm. The concentration be used to research treatment, P1:5400ppm, P2:5900ppm, P3:6400ppm, P4:6900ppm and P5:7400ppm. The Method of this research is a complete random design (RAL) use five treatments and three replications. The main parameter observed lamely fainting time fish and conscious time fish. The result fainting time fish (minute) on P1: 200, 67 P2: 198,33 P3: 196 P4: 193 and P5: 186,67 while results conscious time fish (minute) on P1: 22 P2: 22,67 P3: 23,33 P4: 28,33 and P5: 30,33. Next statistic test use method ANOVA and BNT test with level 5% indicate significantly different, and 1 % indicate very differently real. The obtainable conclusion that research use leaf durian infusum to anesthesia process gurami fish very differently real to fainting time and conscious time. The best treatment on P5(7400ppm) because gurami fish fast to fainting time and long a for conscious time.